2022
DOI: 10.1111/jofi.13105
|View full text |Cite
|
Sign up to set email alerts
|

Predictable Financial Crises

Abstract: Using historical data on postwar financial crises around the world, we show that the combination of rapid credit and asset price growth over the prior three years, whether in the nonfinancial business or the household sector, is associated with a 40% probability of entering a financial crisis within the next three years. This compares with a roughly 7% probability in normal times, when neither credit nor asset price growth is elevated. Our evidence challenges the view that financial crises are unpredictable “b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…risk and right-tail risk, where the AIC is applied to determine the optimal lag order, and then examine the leading-lag relationship between them. For instance,  r Alternatively, right-tail risk has a stronger forward-looking predictive power for left-tail risk, implying that the rapid asset price boom in the short term is indeed a great early warning indicator of financial crises (Borio and Lowe, 2002;Schularick and Taylor, 2012;Krishnamurthy and Li, 2020;Greenwood et al, 2022).…”
Section: Tail Volatility Spillover Effects Across Sectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…risk and right-tail risk, where the AIC is applied to determine the optimal lag order, and then examine the leading-lag relationship between them. For instance,  r Alternatively, right-tail risk has a stronger forward-looking predictive power for left-tail risk, implying that the rapid asset price boom in the short term is indeed a great early warning indicator of financial crises (Borio and Lowe, 2002;Schularick and Taylor, 2012;Krishnamurthy and Li, 2020;Greenwood et al, 2022).…”
Section: Tail Volatility Spillover Effects Across Sectorsmentioning
confidence: 99%
“…As shown in Table 7 , apart from the absence of Granger causality between and , right-tail risk is a one-way Granger cause of left-tail risk in the remaining groups. Alternatively, right-tail risk has a stronger forward-looking predictive power for left-tail risk, implying that the rapid asset price boom in the short term is indeed a great early warning indicator of financial crises ( Borio and Lowe, 2002 ; Schularick and Taylor, 2012 ; Krishnamurthy and Li, 2020 ; Greenwood et al, 2022 ).…”
Section: Empirical Analysis Based On the Tail Volatility Spillover Ne...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies found that the pre-crisis event and impact of the economic and financial crisis in a country can be detected by economic models (Greenwood et al, 2022;Reinhart et al, 2000;Goldstein et al, 2000;Bussiere & Fratzscher, 2002). If it is unpredictable, financial crises can cause severe economic costs in the form of slowing economic growth, decreased output, corporate bankruptcies, layoffs, financial sector instability, decreased credit distribution, and others (Krugman, 1999;Chen & Svirydzenka, 2021;Hutchison & Noy, 2006;Claessens et al, 2012;Claessens & Kose, 2013a;Claessens & Kose, 2013b;IMF, 2022;Pritsker, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Greenwood et al . (2022, p. 863) document that economic crises, including the 2007 financial crisis, are predictable; they argue that their ‘evidence challenges the view that financial crises are unpredictable “bolts from the sky” and supports the Kindleberger‐Minsky view that crises are the byproduct of predictable, boom‐bust credit cycles’. If financial crises are predictable, analysts can use past knowledge to understand when a financial crisis is likely to take place and how it will affect firms’ behaviour.…”
mentioning
confidence: 99%